Heavy metal passivator and its use in fly ash-slag-based backfill material

CN122916485APending Publication Date: 2026-10-16SOUTH CHINA INST OF ENVIRONMENTAL SCI MEP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611200796.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,单一的钝化方法往往存在钝化效率不高、稳定性差、适用范围有限等不足

Benefits of technology

(1)本发明的重金属钝化剂通过科学复配多种功能性成分,能从物理吸附、化学沉淀、螯合络合等多个方面共同作用,通过多重协同钝化机制显著降低重金属离子的迁移性和生物有效性,以高效稳定飞灰-炉渣基回填材料中的重金属离子。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of heavy metal passivator, and particularly relates to a heavy metal passivator and application of the heavy metal passivator in fly ash-slag based backfill material; the raw material of the heavy metal passivator comprises the following components in parts by weight: 40-50 parts of attapulgite, 20-30 parts of polyacrylamide-epoxy succinic acid composite gel particles, 10-20 parts of disodium hydrogen phosphate, 5-10 parts of calcium hydroxide, 4-6 parts of sodium sulfide and 8-12 parts of humic acid. The heavy metal passivator can jointly act from aspects of physical adsorption, chemical precipitation, chelation and complexation through scientific compounding of multiple functional components, significantly reduces migration and bioavailability of heavy metal ions through multiple synergistic passivation mechanisms, and efficiently and stably stabilizes heavy metal ions in fly ash-slag based backfill material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heavy metal passivating agent technology, specifically to a heavy metal passivating agent and its application in fly ash-slag based backfill materials. Background Technology

[0002] With rapid industrial development, the amount of fly ash and slag produced by coal-fired power plants, waste incineration plants, and other factories has increased dramatically. The treatment cost of this fly ash and slag is high, leading to the development of resource utilization methods using them as backfill materials. However, these fly ash and slag contain large amounts of heavy metals, such as lead, cadmium, chromium, and mercury. If used directly as backfill material, these heavy metals can easily leach out into the soil and water bodies under long-term rainwater leaching and groundwater infiltration, causing serious environmental pollution and posing a potential threat to ecosystems and human health.

[0003] Currently, commonly used heavy metal passivation methods mainly include physical adsorption, chemical precipitation, ion exchange, and stabilizing agents. However, single passivation methods often suffer from low passivation efficiency, poor stability, and limited applicability. For example, traditional physical adsorption materials such as activated carbon, while possessing some adsorption capacity for heavy metals, have limited adsorption capacity and are easily desorbed due to environmental factors. Chemical precipitation, although simple to operate, produces precipitates that dissolve easily under acidic conditions, leading to the re-release of heavy metals. Therefore, developing a heavy metal passivating agent that can efficiently stabilize heavy metals through multiple synergistic mechanisms and possesses good environmental adaptability and long-term stability is of great significance for promoting the safe resource utilization of fly ash-slag-based backfill materials. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides a heavy metal passivating agent and its application in fly ash-slag based backfill materials.

[0005] The technical solution of the present invention is: a heavy metal passivating agent, comprising the following components by weight: 40-50 parts of attapulgite, 20-30 parts of polyacrylamide-epoxysuccinic acid composite gel particles, 10-20 parts of disodium hydrogen phosphate, 5-10 parts of calcium hydroxide, 4-6 parts of sodium sulfide, and 8-12 parts of humic acid.

[0006] Note: The above-mentioned heavy metal passivating agent, through the scientific compounding of multiple functional components, can work together from multiple aspects such as physical adsorption, chemical precipitation, and chelation complexation. Through multiple synergistic passivation mechanisms, it can significantly reduce the migration and bioavailability of heavy metal ions, thereby efficiently stabilizing heavy metal ions in fly ash-slag-based backfill materials.

[0007] Furthermore, the preparation method of the polyacrylamide-epoxysuccinic acid composite gel particles includes the following steps: S1. Add acrylamide and sodium epoxy succinate to deionized water and stir for 10-15 minutes to obtain a prepolymer solution; wherein the mass ratio of acrylamide, sodium epoxy succinate and deionized water is 1:0.6-0.8:7-9. S2. Add sodium citrate, methylenebisacrylamide, and ammonium persulfate to the prepolymer solution to obtain a mixed solution; wherein the amount of sodium citrate added is 2-3 wt% of the prepolymer solution, the amount of methylenebisacrylamide added is 0.5-1 wt% of the prepolymer solution, and the amount of ammonium persulfate added is 1-2 wt% of the prepolymer solution. S3. Gradually add the mixture dropwise into the oil phase, then heat the oil phase to 50~60℃ and keep it at this temperature for 4~5 hours with stirring. After the temperature is maintained, let it stand for 12~16 hours, filter, and obtain gel particles; wherein, the mass ratio of the mixture to the oil phase is 1:4~5. S4. The gel particles are washed and then freeze-dried to obtain polyacrylamide-epoxysuccinic acid composite gel particles.

[0008] Note: The above method uses polyacrylamide as the gel particle skeleton, providing good hydrophilicity and spatial network support for the gel particles. The carboxyl and hydroxyl groups in polyepoxysuccinic acid endow the gel particles with excellent chelating ability, which can form stable five-membered ring chelates with heavy metal ions. The prepared polyacrylamide-epoxysuccinic acid composite gel particles can physically adsorb and retain heavy metal ions through a three-dimensional network structure. They can also use the abundant active groups on their surface to undergo specific chelation reactions with heavy metal ions, thereby achieving efficient capture of various heavy metal ions.

[0009] Furthermore, in step S2, the method for preparing the mixture is as follows: S2-1. Heat the prepolymer solution to 40~50℃, then add sodium citrate to the prepolymer solution, stir for 3~5 minutes, and then let the prepolymer solution cool to room temperature. S2-2. Continuously introduce nitrogen gas into the prepolymer solution, then heat the prepolymer solution until it reaches 30~35℃. Add methylenebisacrylamide to the prepolymer solution and stir for 4~8 minutes, then stop introducing nitrogen gas. S2-3. Cool the prepolymer solution until the temperature reaches 1~5℃, then add ammonium persulfate to the prepolymer solution and continue stirring for 1~2 minutes to obtain a mixture.

[0010] Note: The above mixture preparation process effectively ensures the reaction efficiency and stability of each component by precisely controlling the temperature and reaction atmosphere, making the polymerization reaction proceed more smoothly and orderly, thereby ensuring that the final gel particles have a uniform network structure and stable performance.

[0011] Furthermore, in step S3, the oil phase is prepared by mixing cyclohexane and sorbitan oleate, wherein the sorbitan oleate accounts for 1-3% of the mass of cyclohexane.

[0012] Note: The oil phase described above can disperse the mixture into uniform droplets, forming a stable water-in-oil emulsion system. This provides a good microenvironment for the formation of gel particles, ensuring that the generated gel particles are uniform in size and regular in shape, and avoiding particle aggregation or uneven size.

[0013] Further, in step S4, the washing method is as follows: the gel particles are soaked in deionized water, and the deionized water is changed every 4 to 8 hours until the washing is completed after 24 to 48 hours.

[0014] Note: Soaking the gel particles in deionized water multiple times can thoroughly remove residual impurities from the particle surface, preventing these impurities from adversely affecting the performance of the subsequent heavy metal passivating agent.

[0015] Further, in step S4, the freeze-drying method is as follows: the gel particles are kept at a temperature of -40~-30℃ for 10~12h, then the temperature is increased to 0~5℃ at a rate of 1~2℃ / min and kept for 4~5h, then the temperature is increased to 20~25℃ at a rate of 0.5~1℃ / min and kept for 2~4h to complete the freeze-drying.

[0016] Note: The above freeze-drying process can retain the three-dimensional network structure of gel particles to the maximum extent while removing moisture from the particles. This avoids the structural collapse or pore blockage problems that may occur with traditional drying methods, thus ensuring that the composite gel particles have a rich pore structure and a large specific surface area, providing sufficient space and active sites for subsequent adsorption of heavy metal ions.

[0017] Furthermore, the preparation method of the heavy metal passivating agent includes the following steps: 1) Add attapulgite clay, polyacrylamide-epoxysuccinic acid composite gel particles, disodium hydrogen phosphate, calcium hydroxide and sodium sulfide into a mixer according to the weight parts mentioned above and mix for 15-20 minutes to obtain dry material; 2) Add humic acid to deionized water and stir for 5-10 minutes to obtain a humic acid mixture; wherein the mass ratio of humic acid to deionized water is 1:30-35. 3) While stirring, spray the humic acid mixture into the dry material to obtain wet material, and use a granulator to make the wet material into solid particles with a particle size of 1~3mm. 4) Dry the solid particles in a ventilated environment at 40~60℃ for 12~20h to obtain a heavy metal passivating agent.

[0018] Note: The above preparation method, through stepwise mixing and granulation processes, not only achieves uniform dispersion of raw materials, but also ensures that the components in the heavy metal passivating agent can work synergistically and form a stable particulate structure, so as to facilitate uniform mixing in fly ash-slag-based backfill materials, providing favorable conditions for the adsorption and reaction of heavy metal ions.

[0019] On the other hand, the present invention also provides the application of the above-mentioned heavy metal passivating agent in fly ash-slag based backfill materials.

[0020] Note: The above-mentioned heavy metal passivating agent can effectively stabilize heavy metal ions in fly ash-slag-based backfill materials through multiple mechanisms such as physical adsorption, chemical precipitation and chelation complexation, effectively inhibit the migration and diffusion of heavy metals to the surrounding soil and groundwater, thereby reducing the risk of heavy metal pollution and providing a safety guarantee for the resource utilization of solid wastes such as fly ash and slag.

[0021] Furthermore, the application method is as follows: The heavy metal passivating agent is added to the fly ash-slag-based backfill material at a mass ratio of 0.5-3%; the moisture content of the fly ash-slag-based backfill material is 15-20%.

[0022] Note: Limiting the addition ratio and moisture content can ensure the effectiveness of the heavy metal passivating agent while avoiding increased material costs due to excessive addition.

[0023] The beneficial effects of this invention are: (1) The heavy metal passivating agent of the present invention, through scientific compounding of multiple functional components, can work together from multiple aspects such as physical adsorption, chemical precipitation, chelation complexation, etc., and significantly reduce the migration and bioavailability of heavy metal ions through multiple synergistic passivation mechanisms, so as to efficiently stabilize heavy metal ions in fly ash-slag based backfill materials.

[0024] (2) The polyacrylamide-epoxysuccinic acid composite gel particles prepared by the present invention can physically adsorb and retain heavy metal ions through a three-dimensional network structure, and can also use the abundant active groups on its surface to undergo specific chelation reactions with heavy metal ions, thereby achieving efficient capture of a variety of heavy metal ions.

[0025] (3) The heavy metal passivating agent of the present invention can effectively stabilize heavy metal ions in fly ash-slag-based backfill materials through multiple mechanisms such as physical adsorption, chemical precipitation and chelation complexation, effectively inhibit the migration and diffusion of heavy metals to the surrounding soil and groundwater, thereby reducing the risk of heavy metal pollution and providing a safety guarantee for the resource utilization of solid wastes such as fly ash and slag. Detailed Implementation

[0026] To further illustrate the methods and effects of this invention, the technical solution of this invention will be clearly and completely described below in conjunction with experiments.

[0027] Example 1: A heavy metal passivating agent, comprising the following components by weight: 45 parts attapulgite, 25 parts polyacrylamide-epoxysuccinic acid composite gel particles, 15 parts disodium hydrogen phosphate, 8 parts calcium hydroxide, 5 parts sodium sulfide, and 10 parts humic acid. The preparation method of polyacrylamide-epoxysuccinic acid composite gel particles includes the following steps: S1. Acrylamide and sodium epoxy succinate are added to deionized water and stirred for 12 minutes to obtain a prepolymer solution; wherein the mass ratio of acrylamide, sodium epoxy succinate and deionized water is 1:0.7:8. S2. Add sodium citrate, methylenebisacrylamide, and ammonium persulfate to the prepolymer solution to obtain a mixed solution; wherein the amount of sodium citrate added is 2.5 wt% of the prepolymer solution, the amount of methylenebisacrylamide added is 0.8 wt% of the prepolymer solution, and the amount of ammonium persulfate added is 1.5 wt% of the prepolymer solution. The preparation method of the mixture is as follows: S2-1. Heat the prepolymer solution to 45°C, then add sodium citrate to the prepolymer solution, stir for 4 minutes, and then let the prepolymer solution cool to room temperature. S2-2. Nitrogen gas is continuously introduced into the prepolymer solution, and then the prepolymer solution is heated until it reaches 32°C. Then, methylenebisacrylamide is added to the prepolymer solution and stirred for 6 minutes, and then the nitrogen gas is stopped. S2-3. Cool the prepolymer solution until the temperature of the prepolymer solution reaches 3°C, then add ammonium persulfate to the prepolymer solution and continue stirring for 1.5 min to obtain a mixture. S3. The mixture is gradually added dropwise to the oil phase, and then the oil phase is heated to 55°C and kept at this temperature for 4.5 hours with stirring. After the temperature holding period, the mixture is allowed to stand for 14 hours and then filtered to obtain gel particles. The mass ratio of the mixture to the oil phase is 1:4.5. The oil phase is prepared by mixing cyclohexane and sorbitan oleate, with sorbitan oleate accounting for 2% of the mass of cyclohexane. S4. The gel particles are washed and then freeze-dried to obtain polyacrylamide-epoxysuccinic acid composite gel particles. The washing method is as follows: Soak the gel particles in deionized water, and change the deionized water every 6 hours until the washing is completed after 32 hours. The freeze-drying method is as follows: the gel particles are kept at -35℃ for 11 hours, then the temperature is increased to 3℃ at a rate of 1.5℃ / min and kept for 4.5 hours, then the temperature is increased to 22℃ at a rate of 0.8℃ / min and kept for 3 hours to complete the freeze-drying.

[0028] The preparation method of the above-mentioned heavy metal passivating agent includes the following steps: 1) Add attapulgite clay, polyacrylamide-epoxysuccinic acid composite gel particles, disodium hydrogen phosphate, calcium hydroxide and sodium sulfide into a mixer according to the weight parts and mix for 18 minutes to obtain dry material; 2) Add humic acid to deionized water and stir for 8 minutes to obtain a humic acid mixture; wherein the mass ratio of humic acid to deionized water is 1:32. 3) While stirring, spray the humic acid mixture into the dry material to obtain wet material, and use a granulator to make the wet material into solid particles with a particle size of 1~3mm. 4) Dry the solid particles in a ventilated environment at 50°C for 16 hours to obtain a heavy metal passivating agent.

[0029] The above-mentioned heavy metal passivating agent was added to the fly ash-slag-based backfill material at a mass ratio of 2%; the moisture content of the fly ash-slag-based backfill material was 18%.

[0030] Example 2: This example is basically the same as Example 1, except that the heavy metal passivating agent includes the following components by weight: 40 parts of attapulgite, 20 parts of polyacrylamide-epoxysuccinic acid composite gel particles, 10 parts of disodium hydrogen phosphate, 5 parts of calcium hydroxide, 4 parts of sodium sulfide, and 8 parts of humic acid.

[0031] Example 3: This example is basically the same as Example 1, except that the heavy metal passivating agent includes the following components by weight: 50 parts of attapulgite, 30 parts of polyacrylamide-epoxysuccinic acid composite gel particles, 20 parts of disodium hydrogen phosphate, 10 parts of calcium hydroxide, 6 parts of sodium sulfide, and 12 parts of humic acid.

[0032] Example 4: This example is basically the same as Example 1, except that the mass ratio of acrylamide, sodium epoxide succinate and deionized water is 1:0.6:7.

[0033] Example 5: This example is basically the same as Example 1, except that the mass ratio of acrylamide, sodium epoxysuccinate and deionized water is 1:0.8:9.

[0034] Example 6: This example is basically the same as Example 1, except that the prepolymer solution is heated to 40°C and then sodium citrate is added to the prepolymer solution.

[0035] Example 7: This example is basically the same as Example 1, except that the prepolymer solution is heated to 50°C and then sodium citrate is added to the prepolymer solution.

[0036] Example 8: This example is basically the same as Example 1, except that the amount of sodium citrate added is 2 wt% of the prepolymer solution.

[0037] Example 9: This example is basically the same as Example 1, except that the amount of sodium citrate added accounts for 3 wt% of the prepolymer solution.

[0038] Example 10: This example is basically the same as Example 1, except that methylenebisacrylamide is added to the prepolymer solution after the prepolymer solution reaches 30°C.

[0039] Example 11: This example is basically the same as Example 1, except that methylenebisacrylamide is added to the prepolymer solution after the prepolymer solution reaches 35°C.

[0040] Example 12: This example is basically the same as Example 1, except that the amount of methylenebisacrylamide added is 0.5 wt% of the prepolymer solution.

[0041] Example 13: This example is basically the same as Example 1, except that the amount of methylenebisacrylamide added is 1 wt% of the prepolymer solution.

[0042] Example 14: This example is basically the same as Example 1, except that the prepolymer solution is cooled down until the temperature of the prepolymer solution reaches 1°C, and then ammonium persulfate is added to the prepolymer solution.

[0043] Example 15: This example is basically the same as Example 1, except that the prepolymer solution is cooled down until the temperature of the prepolymer solution reaches 5°C, and then ammonium persulfate is added to the prepolymer solution.

[0044] Example 16: This example is basically the same as Example 1, except that the amount of ammonium persulfate added is 1 wt% of the prepolymer solution.

[0045] Example 17: This example is basically the same as Example 1, except that the amount of ammonium persulfate added is 2 wt% of the prepolymer solution.

[0046] Example 18: This example is basically the same as Example 1, except that the mass ratio of the mixture to the oil phase is 1:4.

[0047] Example 19: This example is basically the same as Example 1, except that the mass ratio of the mixture to the oil phase is 1:5.

[0048] Example 20: This example is basically the same as Example 1, except that the gel particles are kept at -40°C for 11 hours, then heated to 0°C at a rate of 1°C / min and kept for 4.5 hours, then heated to 20°C at a rate of 0.5°C / min and kept for 3 hours to complete the freeze drying.

[0049] Example 21: This example is basically the same as Example 1, except that the gel particles are kept at -30°C for 11 hours, then heated to 5°C at a rate of 2°C / min and kept for 4.5 hours, then heated to 25°C at a rate of 1°C / min and kept for 3 hours to complete the freeze drying.

[0050] Example 22: This example is basically the same as Example 1, except that the heavy metal passivating agent is added to the fly ash-slag-based backfill material at a mass ratio of 0.5%.

[0051] Example 23: This example is basically the same as Example 1, except that the heavy metal passivating agent is added to the fly ash-slag-based backfill material at a mass ratio of 3%.

[0052] Comparative Example 1: Referring to Example 1, the polyacrylamide-epoxysuccinic acid composite gel particles were replaced with a mixture of 14 parts polyacrylamide and 11 parts polyepoxysuccinic acid.

[0053] Comparative Example 2: Referring to Example 1, sodium citrate, methylenebisacrylamide and ammonium persulfate were added to the prepolymer solution at 3°C ​​in one step.

[0054] Comparative Example 3: Referring to Example 1, the freeze-drying method was as follows: the gel particles were kept at -40°C for 18.5 hours.

[0055] Experimental Example: The fly ash-slag-based backfill materials used in all the above embodiments and comparative examples were from the same batch. Before adding the heavy metal passivating agent, the leaching content of heavy metal ions in the samples was tested. After adding the heavy metal passivating agent, the samples were stirred evenly and allowed to stand for 24 hours. The leaching content of heavy metal ions in the samples of each embodiment and comparative example was then tested, and the rate of decrease in heavy metal ion content was calculated. The specific investigation is as follows: Experiment Example 1: Investigating the Influence of Raw Material Composition on the Performance of Heavy Metal Passivating Agents Using Examples 1, 2, and 3, as well as Comparative Example 1, as experimental comparisons, the performance of heavy metal passivating agents with different raw material compositions is shown in Table 1 below: Table 1 Performance of heavy metal passivating agents with different raw material compositions

[0056] As shown in Table 1, compared with Examples 1, 2, and 3, the sample of Example 1 showed the highest rate of decrease in the content of each heavy metal ion. This indicates that the heavy metal passivator selected in Example 1 had the best adsorption and chelation effect on heavy metal ions. Therefore, the raw material composition of the heavy metal passivator selected in Example 1 was optimal.

[0057] Compared with Comparative Example 1, in Example 1, after replacing the polyacrylamide-epoxysuccinic acid composite gel particles with an equal weight of a simple mixture of polyacrylamide and polyepoxysuccinic acid, the decrease rate of all heavy metal ions was significantly reduced. This indicates that the polyacrylamide-epoxysuccinic acid composite gel particles prepared in Example 1 are not a simple superposition of their components, but rather a synergistic effect produced through the composite gel structure. Therefore, the heavy metal passivating agent raw material composition selected in Example 1 is optimal.

[0058] Experiment Example 2: Investigating the effect of prepolymer solution composition on the performance of heavy metal passivating agents Using Examples 1, 4, and 5 as experimental comparisons, the performance of heavy metal passivating agents under different prepolymer solution compositions is shown in Table 2 below: Table 2 Performance of heavy metal passivators under different prepolymer solution compositions

[0059] As shown in Table 2, compared with Examples 1, 4, and 5, the sample of Example 1 showed the highest decrease rate in the content of each heavy metal ion. This indicates that under the prepolymer solution composition selected in Example 1, the three-dimensional network structure of the polyacrylamide-epoxysuccinic acid composite gel particles is more regular, the surface active groups are more evenly distributed, and the physical adsorption and retention and specific chelation reaction of heavy metal ions are more effective. Therefore, the prepolymer solution composition ratio selected in Example 1 is optimal.

[0060] Experiment Example 3: Investigating the effects of sodium citrate addition temperature and dosage on the performance of heavy metal passivating agents. Using Examples 1, 6, 7, 8, and 9 as comparative experiments, the performance of heavy metal passivating agents under different addition temperatures and amounts of sodium citrate is shown in Table 3 below: Table 3. Performance of sodium citrate as a heavy metal passivator at different addition temperatures and dosages.

[0061] As shown in Table 3, compared with Examples 1, 6, 7, 8, and 9, the sample of Example 1 showed the highest decrease rate in the content of each heavy metal ion. This indicates that under the sodium citrate addition temperature and amount selected in Example 1, sodium citrate can most effectively regulate the charge distribution of the prepolymer solution, making the pore size and distribution of the composite gel particles more reasonable. Therefore, the sodium citrate addition temperature and amount selected in Example 1 are optimal.

[0062] Experiment Example 4: Investigating the effects of methylenebisacrylamide addition temperature and dosage on the performance of heavy metal passivating agents. Using Examples 1, 10, 11, 12, and 13 as comparative experiments, the heavy metal passivating properties of methylenebisacrylamide at different addition temperatures and amounts are shown in Table 4 below: Table 4. Performance of heavy metal passivating agent at different addition temperatures and dosages of methylenebisacrylamide

[0063] As shown in Table 4, compared with Examples 1, 10, 11, 12, and 13, the sample of Example 1 showed the highest decrease rate in the content of each heavy metal ion. This indicates that under the selected addition temperature and amount of methylene bisacrylamide in Example 1, methylene bisacrylamide can participate in the cross-linking reaction most accurately, and the resulting composite gel particles have moderate mechanical strength and high porosity. Therefore, the addition temperature and amount of methylene bisacrylamide selected in Example 1 are optimal.

[0064] Experiment Example 5: Investigating the effects of ammonium persulfate addition temperature and dosage on the performance of heavy metal passivating agents. Using Examples 1, 14, 15, 16, 17 and Comparative Example 2 as experimental comparisons, the performance of heavy metal passivating agents under different addition temperatures and amounts of ammonium persulfate is shown in Table 5 below: Table 5. Performance of heavy metal passivating agents under different addition temperatures and dosages of ammonium persulfate

[0065] As shown in Table 5, compared with Examples 1, 14, 15, 16, and 17, the sample of Example 1 showed the highest decrease rate in the content of each heavy metal ion. This indicates that under the selected ammonium persulfate addition temperature and amount in Example 1, ammonium persulfate can initiate the polymerization reaction at the most suitable rate, so that the degree of polymerization and crosslinking density of the prepolymer solution reach the best balance. Therefore, the selected ammonium persulfate addition temperature and amount in Example 1 are optimal.

[0066] Compared with Comparative Example 2, in Example 1, the decrease rate of all heavy metal ions was significantly lower than that in Example 1 after sodium citrate, methylenebisacrylamide and ammonium persulfate were added to the prepolymer solution at a specific temperature at one time. This indicates that the stepwise addition method in Example 1 can ensure the orderly progress of each reaction during the formation of composite gel particles. Therefore, the preparation method of polyacrylamide-epoxysuccinic acid composite gel particles selected in Example 1 is the optimal one.

[0067] Experiment Example 6: Investigating the effect of the ratio of the mixture to the oil phase on the performance of heavy metal passivating agents. Using Examples 1, 18, and 19 as comparative experiments, the performance of heavy metal passivating agents with different ratios of the mixture to the oil phase is shown in Table 6 below: Table 6 Performance of heavy metal passivators at different ratios of mixture to oil phase

[0068] As shown in Table 6, compared with Examples 1, 18, and 19, the sample of Example 1 showed the highest decrease rate in the content of each heavy metal ion. This indicates that the mixed liquid to oil phase ratio selected in Example 1 resulted in the most uniform particle size distribution and the best interfacial tension control effect, effectively avoiding particle agglomeration. This provides a good microstructure basis for subsequent freeze-drying and heavy metal adsorption. Therefore, the mixed liquid to oil phase ratio selected in Example 1 is optimal.

[0069] Experiment Example 7: Investigating the effect of freeze-drying parameters on the performance of heavy metal passivating agents. Using Examples 1, 20, 21 and Comparative Example 3 as experimental comparisons, the performance of heavy metal passivating agents under different freeze-drying parameters is shown in Table 7 below: Table 7 Performance of heavy metal passivating agents under different freeze-drying parameters

[0070] As shown in Table 7, compared with Examples 1, 20, and 21, the sample of Example 1 showed the highest decrease rate in the content of each heavy metal ion. This indicates that under the freeze-drying parameters selected in Example 1, the ice crystal sublimation process inside the composite gel particles was the most thorough, resulting in a well-developed and interconnected pore structure. This maximizes the preservation of the specific surface area and active adsorption sites of the composite gel particles. Therefore, the freeze-drying parameters selected in Example 1 are optimal.

[0071] Compared with Comparative Example 3, Example 1 showed that after the freeze-drying temperature was kept constant, the decrease rate of each heavy metal ion content was significantly reduced, indicating that the freeze-drying parameters used in Example 1 could better protect the pore structure of the composite gel particles. Therefore, the freeze-drying parameters selected in Example 1 were optimal.

[0072] Experiment Example 8: Investigating the effect of addition amount on the performance of heavy metal passivating agents Using Examples 1, 22, and 23 as comparative experiments, the performance of heavy metal passivating agents with different addition amounts is shown in Table 8 below: Table 8 Performance of heavy metal passivators at different addition levels

[0073] As shown in Table 8, compared with Examples 1, 22, and 23, the decrease rate of each heavy metal ion content in the sample increased with the increase of the amount of heavy metal passivating agent added. However, with the continued increase of the amount of heavy metal passivating agent added, the decrease rate of each heavy metal ion content in the sample began to show no significant change. Therefore, from a cost perspective, the amount of heavy metal passivating agent added selected in Example 1 is optimal.

Claims

1. A heavy metal passivating agent, characterized in that, The composition by weight is as follows: 40-50 parts attapulgite, 20-30 parts polyacrylamide-epoxysuccinic acid composite gel particles, 10-20 parts disodium hydrogen phosphate, 5-10 parts calcium hydroxide, 4-6 parts sodium sulfide, and 8-12 parts humic acid.

2. The heavy metal passivating agent according to claim 1, characterized in that, The preparation method of the polyacrylamide-epoxysuccinic acid composite gel particles includes the following steps: S1. Add acrylamide and sodium epoxy succinate to deionized water and stir for 10-15 minutes to obtain a prepolymer solution; wherein the mass ratio of acrylamide, sodium epoxy succinate and deionized water is 1:0.6-0.8:7-9. S2. Add sodium citrate, methylenebisacrylamide, and ammonium persulfate to the prepolymer solution to obtain a mixed solution; wherein the amount of sodium citrate added is 2-3 wt% of the prepolymer solution, the amount of methylenebisacrylamide added is 0.5-1 wt% of the prepolymer solution, and the amount of ammonium persulfate added is 1-2 wt% of the prepolymer solution. S3. Gradually add the mixture dropwise into the oil phase, then heat the oil phase to 50~60℃ and keep it at this temperature for 4~5 hours with stirring. After the temperature is maintained, let it stand for 12~16 hours, filter, and obtain gel particles; wherein, the mass ratio of the mixture to the oil phase is 1:4~5. S4. The gel particles are washed and then freeze-dried to obtain polyacrylamide-epoxysuccinic acid composite gel particles.

3. The heavy metal passivating agent according to claim 2, characterized in that, In step S2, the method for preparing the mixture is as follows: S2-1. Heat the prepolymer solution to 40~50℃, then add sodium citrate to the prepolymer solution, stir for 3~5 minutes, and then let the prepolymer solution cool to room temperature. S2-2. Continuously introduce nitrogen gas into the prepolymer solution, then heat the prepolymer solution until it reaches 30~35℃. Add methylenebisacrylamide to the prepolymer solution and stir for 4~8 minutes, then stop introducing nitrogen gas. S2-3. Cool the prepolymer solution until the temperature reaches 1~5℃, then add ammonium persulfate to the prepolymer solution and continue stirring for 1~2 minutes to obtain a mixture.

4. The heavy metal passivating agent according to claim 2, characterized in that, In step S3, the oil phase is prepared by mixing cyclohexane and sorbitan oleate, wherein the sorbitan oleate accounts for 1-3% of the mass of cyclohexane.

5. A heavy metal passivating agent according to claim 2, characterized in that, In step S4, the washing method is as follows: the gel particles are soaked in deionized water, and the deionized water is changed every 4 to 8 hours until the washing is completed after 24 to 48 hours.

6. The heavy metal passivating agent according to claim 2, characterized in that, In step S4, the freeze-drying method is as follows: the gel particles are kept at a temperature of -40~-30℃ for 10~12h, then the temperature is increased to 0~5℃ at a rate of 1~2℃ / min and kept for 4~5h, then the temperature is increased to 20~25℃ at a rate of 0.5~1℃ / min and kept for 2~4h to complete the freeze-drying.

7. The heavy metal passivating agent according to claim 1, characterized in that, The preparation method of the heavy metal passivating agent includes the following steps: 1) Add attapulgite clay, polyacrylamide-epoxysuccinic acid composite gel particles, disodium hydrogen phosphate, calcium hydroxide and sodium sulfide into a mixer according to the weight parts mentioned above and mix for 15-20 minutes to obtain dry material; 2) Add humic acid to deionized water and stir for 5-10 minutes to obtain a humic acid mixture; wherein the mass ratio of humic acid to deionized water is 1:30-35. 3) While stirring, spray the humic acid mixture into the dry material to obtain wet material, and use a granulator to make the wet material into solid particles with a particle size of 1~3mm. 4) Dry the solid particles in a ventilated environment at 40~60℃ for 12~20h to obtain a heavy metal passivating agent.

8. The application of the heavy metal passivating agent as described in any one of claims 1 to 7 in fly ash-slag based backfill materials.

9. The application according to claim 8, characterized in that, The application method is as follows: add the heavy metal passivating agent to the fly ash-slag-based backfill material at a mass ratio of 0.5-3%; the moisture content of the fly ash-slag-based backfill material is 15-20%.